(NrASSKAZY I POWESTI(B: [1880-1888] / s (N~ASTX (B1s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B: s (NpRAWDA(B, s, 1984)
(Nw PERWYJ TOM sO^INENIJ WELIKOGO RUSSKOGO PISATELQ a(B. (Np(B. (N~EHOWA (B(1860-1904) (NWO[LI RASSKAZY I POWESTI(B, (NNAPISANNYE W (B1880-1888 (NGG(B.s
rus
Keywords: (NrASSKAZY(B, (NPOWESTIs